How entrepreneurs learn in their region: Entrepreneurial strategies, financialisation and narrative learning in the Vienna biotechnology cluster - Maximilian Fochler (Triple Helix, 2018)
How entrepreneurs plan their business and build their companies plays a central role in how academia-industry-government relations are shaped in a particular region. But how do specific regional styles of building companies and understanding these relations develop? This paper conceptualises the entrepreneurs in a cluster as a community of practice and shows that narrative learning in this community of practice plays a crucial role in how they develop their strategies. Entrepreneurs consider and learn from stories about past successes and failures in the cluster. In particular, they engage with these stories to make sense of what they strive for in building a successful company. Dealing with the complex dynamics of financialisation plays a crucial role in this learning process. This paper is empirically based on biographical interviews with entrepreneurs and serial entrepreneurs in the Vienna biotechnology cluster.
Keywords: 330; Academia/industry relations; Cluster; Venture capital; Entrepreneur; Biotechnology; Learning; Financialisation